EFEKTIFITAS PENYUSUNAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI) PADA SATUAN KERJA KEMENTERIAN AGAMA KOTA BINJAI - Nasution, Indah Juli; Br Purba, Rahima; Maisyarah, Renny (Transpublika Publisher, 2024)
This research aims to analyze the implementation of the agency level financial application system (SAKTI) in order to increase the effectiveness of preparing financial reports in the Binjai City Ministry of Religion work unit. The research approach used is descriptive research. This research was conducted at the Work Unit at the Ministry of Religion (Kemenag) Binjai City which is located at Jalan Jenderal Gatot Subroto No. 55, Limau Mungkur, West Binjai District, Binjai City. The data used is primary data, and the second is secondary data. This research uses the independent variable, Implementation of the Institutional Level Financial Application System and the dependent variable, namely the Effectiveness of Preparing Financial Reports. Data collection techniques are observation, interviews and documentation. The data analysis technique used is descriptive statistical analysis. The results of this research show that the Binjai City Ministry of Religion work unit has implemented the SAKTI application since the beginning of 2022, although it is still very new, its implementation is quite effective and optimal, but employees still need more knowledge so that its application can be maximized.